A Portable Fluorescent Hydrogel-Based Device for On-Site Quantitation of Organophosphorus Pesticides as Low as the Sub-ppb Level - Wang, Tuhui; Zhang, Lening; Xin, Hua (Frontiers in Chemistry, 2022)
Portable devices possess powerful application prospects in on-site sensing without the limitation of bulky instrument. Given the relevance of pesticides with food safety, we herein fabricated a robust gold nanoclusters (AuNCs)-based hydrogel test kit for precisely quantified chlorpyrifos by using three-dimensional (3D) printed subsidiary device. In this work, the fluorescence of AuNCs-based hydrogel could be efficiently quenched by cobalt oxyhydroxide nanoflakes (CoOOH NFs) through Förster resonance energy transfer effect. Chlorpyrifos as acetylcholinesterase inhibitor control the enzymatic hydrolysis reaction, further regulate the production of thiocholine that could decompose CoOOH NFs into Co2+, resulting in fluorescence response of AuNCs-based hydrogel. By employing a home-made subsidiary device and smartphone, the fluorescence color was transformed into digital information, achieving on-site quantitative detection of chlorpyrifos with the detection limit of (LOD) 0.59 ng mL-1. Owing to specific AuNCs signatures and hydrogel encapsulation, the proposed fluorescence hydrogel test kit displayed high sensitivity, good selectivity and anti-interference capability in real sample analysis, providing great potential in on-site application.